ADVANCED DEVELOPMENT MODEL OF TERRITORIAL HUMAN RESOURCES POTENTIAL - Alexander G. Моkronosov; Alexander A. Vershinin (Образование и наука)
The aim of the study is to substantiate the need for eliminating the excessive spatial polarization of territorial socio-economic development as a necessary condition for advanced development of human resources potential. The authors explore the basic problems and contradictions of modern regional and local labor markets in Russia. Based on generalization and systematization of foreign and domestic research outcomes, the paper reveals the main condition for eliminating the territorial polarization threats, which implies formation of a new institutional environment in order to provide co-operation of participants in the territorial interest zone in personnel training and new jobs creating.The research findings demonstrate the increased disproportions between the workforce and labor markets of municipal formations in Sverdlovsk region, and emphasize the need for territorial industrial educational clusters maximizing the network co-operation of the involved parties.The scientific novelty combines adaptation of theoretical concepts of the “new economic geography” applied to reorganization processes in the Russian economy; and elaboration of the cluster model of advanced development of territorial human resources potential by means of territorial centers coordinating the interests of administration, business society, and households.Practical significance of the research results is related to facilitating the administrative efficiency of regional and municipal formations, employers, territorial employment centers, and thereby the advanced development of human resources potential.